Contribution of leg muscle forces to paddle force and kayak speed during maximal effort flat-water paddling - Nilsson, J. E.; Rosdahl, H. G. (International Journal of Sports Physiology and Performance, 2016)
The purpose was to investigate the contribution of leg-muscle-generated forces to paddle force and kayak speed during maximal-effort flat-water paddling. Five elite male kayakers at national and international level participated. The participants warmed up at progressively increasing speeds and then performed a maximal-effort, non-restricted, paddling sequence. This was followed after five minutes' rest by a maximal-effort paddling sequence with the leg action restricted i.e. the knee joints "locked". Left- and right-side foot-bar and paddle forces were recorded with specially designed force devices. In addition, knee angular displacement of the right and left knee was recorded with electrogoniometric technique and the kayak speed was calculated from GPS signals sampled at 5Hz. The results showed that reduction in both push and pull foot-bar forces resulted in a reduction of 21% and 16% in mean paddle stroke force and kayak mean speed, respectively. Thus, the contribution of foot-bar force from lower limb action significantly contributes to the kayakers paddling performance.